Improve Beginning Reading Skills Through Braille Rotary Wheel Media for Blind Children - Faiqah Dzakiyatus Safna; Damri Damri; Asep Ahmad Sopandi; Johandri Taufan (Edumaspul: Jurnal Pendidikan, 2024)
The problem was motivated by the discovery of blind students in SLBN 1 Alahan Panjang class VII who were unable to read words with braille vowel consonant (KVKV) vowel consonant patterns. As a result, the student is still in phase A. The purpose of the research is to find out the braille rotary wheel media in improving initial reading with the KVKV pattern. Single Subject Research (SSR) is a method that will be carried out by researchers with research design A-B-A. Variable (Y) of this study is the ability to read the beginning of braille while variable (X) is braille rotary wheel media. Data collection techniques are carried out using observations and deeds tests, while data collection tools are checklist instruments loaded in the form of percentage scores. The results obtained explain that the ability to read the beginning of braille in baseline conditions (A1) percentage of test results (38%-44%), intervention conditions (50%-63%) and baseline conditions (A2) percentage of test results (66%-77%). The conclusion obtained is that there is an increase in initial reading after the use of braille rotary wheel media.